Farmers' co-learning for effective agroforestry and improved animal welfare in Humbo District, Ethiopia - Berhe, Tsega; Gelan, Eyob; Mokria, Mulugeta; Alemayehu, Gezahegn; Doyle, Rebecca (International Livestock Research Institute, 2024)
The International Livestock Research Institute (ILRI) is implementing the the Scaling Agroforestry to Benefit the Welfare of Animals and their Owners in Ethiopia (SAWA) project to improve food security, income and well-being for families by integrating livestock in sustainable agroecological practices. Running from 2022–2024, the key component of the SAWA Ethiopia project is facilitating farmers’ co-learning platforms to enhance understanding and practice of agroforestry and animal welfare. The co-learning sessions are strategically organized to facilitate collaborative learning. This includes creating real ‘communities of practice’ where farmers share their experiences, learn from each other and expand their social networks, thereby collaboratively generating knowledge. This approach is aimed at reducing gaps in knowledge and experience, as well as observing changes in awareness among farmers. Building linkages among farming groups provides checks and balances that can be applied on the spot, rather than waiting to learn from other sources. Furthermore, co-learning uses locally available knowledge and resources to make workflow more efficient. ILRI, in collaboration with World Agroforestry (ICRAF) and local partners, conducted the farmers’ co-learning initiative on agroforestry and animal welfare in four ‘kebeles’ (wards) of Humbo District. SAWA project beneficiaries were organized into groups so that they could actively participate in research and decision-making on agroforestry. The project also served as a platform for farmers to improve community well-being through the implementation of actions that effect positive change. This report presents the methodology employed, key learnings and insights gathered from the co-learning process, and outlines the way forward. Ultimately, this report seeks continuous follow-up and support from government experts and project partners in helping communities develop sustainable and locally adapted solutions that improve livelihoods and enhance agroecosystem resilience.